(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Technological advances of the Internet and network technology have allowed the development and deployment of new services as multipoint multimedia applications: long-distance education, IPTV, distributed games and videoconferencing systems. In this paper, we focus on videoconferencing systems, which represents the most complex type of video communication. These systems have been used for several of years in business, and more recently in everyday life and they allow interactive communications and facilitate the joint work among users regardless of their geographical location. In this paper, we describe a variety of proposed videoconferencing solutions and classify them according to characteristics such as network architectures and video coding technologies and we propose a novel hybrid cloud and P2P architecture with introduction a function for QoS Adaptation.